Study drug utilization in chronic kidney disease at outpatient pharmacy unit of Hospital Tengku Ampuan Rahimah, Klang, Selangor / Nur Alia Mohd Abd Musthalib - Mohd Abd Musthalib, Nur Alia (2015)
Drug utilization study is a study that analyze the prescribing and dispensing process besides give impact in the management of drugs to provide effective drug therapy. The aim of this study was to identify pattern of drugs prescribed, numbers of medication used and dosage of drug prescribed for Chronic Kidney Disease patient in Hospital Tengku Ampuan Rahimah, Klang besides describe any drug related problem may present in the prescriptions.